KONSUMSI PROTEIN HEWANI DAN PROTEIN NABATI TERHADAP PENYEMBUHAN RUPTUR PERNIEUM: SCOPING REVIEW - Azizah Nafisya Zahratul Jannah; Khamidah Achyar; Mutiara Ramadhani; Repa aulia Pebriyanti; Laelita Intan Maryani (SINERGI : Jurnal Riset Ilmiah, 2026)
Background: Vaginal delivery frequently results in obstetric injury, particularly perineal rupture, which is classified as an acute wound demanding suturing and optimal healing. This healing process is highly dependent on maternal nutritional status, especially protein intake, which is essential for cell regeneration and collagen synthesis. Although animal protein is widely recognized for this role, there is still a need to comprehensively compare its effectiveness with vegetable protein, considering the availability and economic aspects of plant-based sources. Objective: This Scoping Review aims to analyze and compare the differing effects. of high intake patterns of animal protein versus vegetable protein on the clinical parameters of perineal rupture healing in postpartum mothers. Methods: A systematic literature search, guided by the PEOS framework (Population: Postpartum Mothers, Exposure: Animal and Vegetable Protein Intake, Outcome: Perineal Wound Healing), was conducted across four major databases (PubMed, Google Scholar, ScienceDirect, and Wiley) with al publication window of 2020-2025. Five articles. meeting the quality criteria (Hawker instrument) were included, covering animal protein interventions (Egg Whites, Skim Milk, Snakehead Fish Extract) and vegetable protein (Almonds). Results and Conclusion: All studies demonstrated that protein. consumption significantly influences perineal wound healing. Both protein interventions (animal and vegetable sources) were proven effective in accelerating wound healing, which quantitatively measured using Quasi-Experimental methods and specific clinical instruments such as the REEDA Scale and observation of healing time acceleration. Protein supplementation is thus concluded to be a fundamental and measurable nutritional strategy to enhance the quality of postpartum recovery.